IMPLEMENTATION OF HEALTH PROTOCOLS BY THE COMMUNITY DURING RAMADHAN AND EID AL-FITR 2021 - Muhammad Safrudin Musthofa; Muhammad Ivan Rizki; Nugroho Hasan; Alfian K Mustafa; Ananda R Widodo; Eksa Rusdiyana (Universitas Sebelas Maret (UNS), 2022)
Covid-19 pandemic has changed human habit and mindset throughout world. Covid-19 has infected millions people globally in short period of time. This research aims to analyze the implementation of health protocols during Ramadhan and Eid al-Fitr celebration in the people of Karanganyar Regency, Central Java. This research used a descriptive qualitative approach, and data was collected using google form to be analyzed later with percentage tabulation. The result shows that during Ramadhan, the implementation of health protocols involving wearing mask, washing hand with soap, limiting the activity of breaking the fast together reached 80.3% (self-protection), 70.8% (protection of others), but the enforcement of health protocols during Eid al-Fitr celebration reached 44.2% only. It is related to the society value still upholding the cultures of silaturahim(making friendship), shaking hand, and visiting each other.